Prevalence and characterization of community-associated Staphylococcus aureus isolates from human mastitis in Beijing, China - Jihong Gu; Mengyuan Xiong; Jing Zhang; Yirong Li (Elsevier, 2024)
Objectives: Staphylococcus aureus (S. aureus) spreads worldwide and occurrence of mastitis caused by it holds significant implications for public health. We aim to reveal the molecular typing, antibiotic resistance and virulence gene profile of S. aureus causing mastitis through investigation. Methods: A total of 200 isolates of S. aureus were collected from outpatients infected with mastitis in a hospital in Beijing from 2020.7 to 2021.7. The molecular characteristics were analyzed by MLST and spa typing, virulence genes were screened by PCR, antibiotic susceptible test was performed by VITEK® 2 Compact system and phylogenetic analysis was performed by MEGA11 and iTOL. Results: Nineteen sequence types (STs) belonging to 9 clone complexes (CCs) were identified. ST22 was the most dominant clone (77.0%, 154/200). MRSA accounted for 19.0% (38/200) and 89.5% (34/38) of MRSA isolates belonged to CC22 and CC59. The isolates had relatively low levels of antibiotic resistance, with the exception of β-lactams and macrolides with resistance rates above 50.0%. The carrying rate of pvl in the ST22-MRSA strains were 84.2% and the detection rates of seb and pvl in the MRSA isolates were significantly higher than those in the MSSA isolates, while the hlg, fnbA and sdrD showed opposite results. Whole genome sequenced specimens of MRSA strains X4 and B5 show the same evolutionary origin as ST22 EMRSA-15 (HE681097), which is popular in Europe. Conclusions: The method based on molecular epidemiology is an important tool for tracking the spread of S. aureus infections. We need to be alert to the major MRSA clones CC22 and CC59 in the region and be vigilant to the possible pandemic and spread of ST22 EMRSA-15.